Production of recombinant protein by gene cloning from mammalian cell culture - Bakhtiar, M. Taher; Arief Ichwan, Solachuddin Jauhari (2010)
Cancer is defined as a group of neoplastic diseases broadly characterized by abnormalities of cellular differentiation, maturation and control of growth. Cancer significantly contributes to the bulk of deaths globally. It is the number two killer,after cardiovascular disease.The p53 tumor suppressor protein plays a central role in the cellular response to DNA damage by controlling genes involved in cell cycle arrest and apoptosis. The mutation of p53 is one of the most common events found in human cancers. When p53 is lost of its function this may permit the cell to divide without control.